Efektivitas Problem-based Learning Berbantuan Media Pembelajaran Kartu Etnomatematika Batik Jombangan dalam Meningkatkan Motivasi Belajar Peserta Didik SMP - Umardiyah, Fitri; Zuhriawan, M. Qoyum; Satiti, Wisnu Siwi (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
Geometric transformation material requires the role of imagination to link theoretical concepts with real examples. The PBL model can be a means for students to be more active in solving geometric problems, but abstract geometric concepts need to be combined with surrounding objects. One of the surrounding objects that has the concept of geometric transformation is the Jombangan batik cloth. The aim of this research is to determine the effectiveness of problem-based learning assisted by Jombangan batik ethnomathematics cards in increasing junior high school students' learning motivation on geometric transformation material. This research uses a quantitative approach type one-group pretest-posttest design. The research subjects were 32 students in class 7A of Al-Furqon Middle School. Researchers used Jombangan batik ethnomathematics card media as a medium for PBL learning on geometric transformation material. Furthermore, the research instruments used were pretest and posttest learning motivation questionnaires and learning outcomes tests. The data analysis technique used is the paired sample t-test from the results of the learning motivation questionnaire and is supported by learning outcome test scores. Based on the results of the hypothesis test, a significance value of 0.001 (0.001 < 0.05) was obtained, so it can be concluded that PBL learning assisted by Jombangan batik ethnomathematics cards is effective in increasing students' learning motivation on geometric transformation material. The results of the hypothesis test are supported by the results of student learning tests where 90% of students obtained a score above 75.